2022
DOI: 10.3389/fpubh.2022.871722
|View full text |Cite
|
Sign up to set email alerts
|

The impact factors of social media users' forwarding behavior of COVID-19 vaccine topic: Based on empirical analysis of Chinese Weibo users

Abstract: IntroductionSocial media, an essential source of public access to information regarding the COVID-19 vaccines, has a significant effect on the transmission of information regarding the COVID-19 vaccines and helps the public gain correct insights into the effectiveness and safety of the COVID-19 vaccines. The forwarding behavior of social media users on posts concerned with COVID-19 vaccine topics can rapidly disseminate vaccine information in a short period, which has a significant effect on transmission and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Public knowledge was limited due to a lack of information about, inexperience with, and poor awareness of the nature of the virus. Text-based data on social media platforms contain rich information about public opinion and sentiment [ 8 ]. As of September 2022, the number of monthly active users of microblogging platforms reached 584 million, with mobile use accounting for 95%, and the number of daily active users reached 253 million.…”
Section: Introductionmentioning
confidence: 99%
“…Public knowledge was limited due to a lack of information about, inexperience with, and poor awareness of the nature of the virus. Text-based data on social media platforms contain rich information about public opinion and sentiment [ 8 ]. As of September 2022, the number of monthly active users of microblogging platforms reached 584 million, with mobile use accounting for 95%, and the number of daily active users reached 253 million.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to analyze public sentiments and perceptions on COVID-19 vaccines adhering to the staged process of the vaccination campaign using Chinese social media data. Most other studies using social media to examine public opinions of COVID-19 vaccines in different countries were conducted with data that were either collected before the national vaccination rollout [13,14,75] or did not cover the entire vaccination campaign [16,50,76]. Therefore, changes in public opinions at different points in the campaign could not be captured.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Chien et al found that trends in public vaccination emotions were significantly associated with increasing trends in vaccination rates and falling trends in COVID-19 case growth and morbidity and mortality rates [74]. Other scholars have studied the relationship between emotions and reposting behavior in the context of COVID-19, and Sun et al found that posts with negative emotions related to the COVID-19 vaccine were more likely to be reposted on social media, and special attention should be paid to such posts to mitigate the negative effects of the information epidemic [75].…”
Section: Sentiment Analysismentioning
confidence: 99%